2000
DOI: 10.1136/jech.54.12.899
|View full text |Cite
|
Sign up to set email alerts
|

Changing mortality patterns in East and West Germany and Poland. II: Short-term trends during transition and in the 1990s

Abstract: Objectives-To examine trends in life expectancy at birth and age and cause specific patterns of mortality in the former German Democratic Republic (GDR) and Poland during political transition and throughout the 1990s in both parts of Germany and in Poland. Methods-Decomposition

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
58
0
2

Year Published

2003
2003
2022
2022

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(63 citation statements)
references
References 27 publications
3
58
0
2
Order By: Relevance
“…Only from 1990 onwards -the cohorts in our analysis were already at least 53 years old -did institutional arrangements start to converge, although large differences remain, for example in the labour markets. In the light of the observed convergence in total mortality (Nolte, Shkolnikov, and McKee, 2000), we note that this convergence appears to be nearly perfect conditional on our measure of socio-economic status. A natural interpretation of this would be an income effect: Reunification brought about much higher real incomes for pensioners and 12 years were enough to wipe out any lagged effects.…”
Section: Life Expectancy At Age 65 By Epmentioning
confidence: 99%
See 1 more Smart Citation
“…Only from 1990 onwards -the cohorts in our analysis were already at least 53 years old -did institutional arrangements start to converge, although large differences remain, for example in the labour markets. In the light of the observed convergence in total mortality (Nolte, Shkolnikov, and McKee, 2000), we note that this convergence appears to be nearly perfect conditional on our measure of socio-economic status. A natural interpretation of this would be an income effect: Reunification brought about much higher real incomes for pensioners and 12 years were enough to wipe out any lagged effects.…”
Section: Life Expectancy At Age 65 By Epmentioning
confidence: 99%
“…Our findings are consistent with the converging mortality experiences in both regions that have been documented by several authors (cf. for example Nolte et al (2000)). …”
Section: Life Expectancy At Age 65 By Epmentioning
confidence: 99%
“…53,54 Studies from Eastern Europe also suggested a rapid response to changes in lifestyle and diet. 55 Induction periods may be shorter when other causal factors are common. 56 In Beijing, blood pressure and male smoking levels Figure 2.…”
Section: Cholesterol Diabetes Obesity and Dietmentioning
confidence: 99%
“…Health differences exist between sexes, between social groups within countries, and between countries. The patterns of these health differences change as living conditions evolve (Hertzman and Siddiqi 2000;Marmot and Bobak 2000;Marmot and Feeney 1997;Tomatis 2001), as demonstrated by the sharp decline in life expectancy-as well as the widening gap of life expectancy between sexes-in Eastern Europe during the recent political transition (Marmot and Bobak 2000;Nolte et al 2000aNolte et al , 2000b. Thus, observing inequalities in health allows us to better understand how changes in society translate into changes in health.…”
mentioning
confidence: 99%